The mediating role of school bonds in the relationship between psychological toughness and aggression in female high school students - maryam ghafouri; Fatemeh Mosadeghi Nik (Institute of Management fekrenoandish, 2021)
Extended AbstractAbstractThe aim of this study was to determine the mediating role of school bonding in the relationship between psychological toughness and aggression. The method of this study was descriptive-correlative. The statistical population of the study was the second female high school students in Ramsar. A total of 217 students were selected as the statistical sample size by cluster sampling. Data collection tools were Rezaei Sharif and Hajiloo School Connection Questionnaires (2016), Long and Golett Psychological Hardiness(2003), and Eiseng and Glenn Wilson Aggression (1975), which were validated by academic experts and their reliability was confirmed by Cronbach alpha coefficient test. The structural equation technique was used to analyze the data, using Lisrel statistical software and Spss statistical software. Quantitative findings of testing the research hypotheses showed that there is a positive and significant relationship between psychological toughness and school bonding. There is a negative and significant relationship between school bonding and students' aggression. There is a negative and significant relationship between psychological toughness and student aggression, and finally, the link with school has played a mediating role in the relationship between psychological toughness and aggression of the student.IntroductionToday, education, either in general or specific, is an important part of every person's life, and the quality and quantity of education also plays an important role in the future of the individual. Therefore, the psychologists have spent nearly one century to identify exhaustively the predictive factors of academic achievement. Awareness of students' psychological aspects can act as a powerful teaching aid tool. For example, understanding how students behave in certain situations can increase effectiveness of educational tools as well as teacher training methods and education system and finally students' progress (Hamedi Nasab., & Asgari, 2020). Students' academic achievement is one of the important indicators and criteria for the efficiency of the educational system, and therefore the analysis of related factors is one of the most basic research topics in the education system. The study and review of already-done researches shows that academic achievement is not the result of one single factor but several factors affect this variable. Communication with the school can be defined as the extent to which students feel satisfied with being in school; Relationship with the school is defined as students' perception of school support that has a favorable atmosphere and a supportive culture (Rezaei Sharif, Hajloo, 2016). On the other hand, connection with school includes the definition of participation in school, commitment to valued principles, and beliefs to school, and the mental feeling of being accepted, encouraged by others in the classroom, and the feeling that one is an important part of classroom activity. Also, the concept of connection with the school includes the connection of students' experiences with the school, the feeling of security in it, receiving respect from teachers, attachment to the school, the level of participation and involvement in the school and commitment to school values and beliefs (Jafari Harand & et al. 2019). Meanwhile, aggression among children and adolescents is a serious social problem rapidly spread in recent years (World Health Organization, 2015). Aggression and violence exist from childhood and are kept on over time and continue into adolescence and adulthood; so that the highest emergence of aggression is in adolescence (Shakeri, et al., 2019). Aggression weakens the regulation and management of emotions, expressing inappropriate behaviors and emotions, slowing down mental processing and hasty and inappropriate decision making (Jalil, et al., 2017). Hardiness is a set of personality traits introduced by Cubasa (1979) and acts as a source of resistance to stressful life events. This personality variable consists of three interrelated components including commitment, control, and challenge. People with high stubbornness feel more committed to whatever they do, and dedicate themselves to the goal (commitment) in addition to feeling in control of the situation (control) and considering the challenges and limitations of life as an opportunity to grow (challenge) (Hashemi, et al., 2019). Psychological stubbornness creates a certain inner attitude that on the one hand affects a person's view of his abilities and on the other hand has a positive effect on how a person performs among peers and the community. The characteristics such as significant curiosity, the desire to have interesting and meaningful experiences, the belief in the effectiveness of what is mentally imagined, the expectation that changing is natural, and any important stimulus can lead to growth and development can affect academic and social performance. (Azimi, et al., 2018). Based on the above, the researcher tries to answer the question of whether there is a significant relationship between psychological stubbornness and aggression of high school female students with the mediating role of bonding with school.Theoretical frameworkZhang (2010) states that stubbornness is associated with five major personality factors; So that the three components of stubbornness (commitment, control and challenge) have a negative and significant relationship with neuroticism and a positive and significant relationship with the other four personality factors (extraversion, delightedness, pleasantness and conscientiousness). Psychological toughness also reduces depression and anxiety. Psychological hardiness reduces test anxiety and increases students' academic achievement (Azimi, et al., 2018). Social psychologists define aggressive behavior as conscious behavior aimed at inflicting physical or mental suffering. This behavior should not be confused with the prove-oneself-to-others, although many people roughly call others aggressive (Sharifi, S.2017).MethodologyThe research method is descriptive-correlative in nature and applicable in terms of purpose. The statistical population of the study consists of 1774 female students studying in the second secondary school of Ramsar city in the 1300-1400academic year. Due to the large size of the statistical population, three schools were randomly selected and one classroom was selected from each school, which included the tenth, eleventh and twelfth grades. A total of 9 classrooms were selected with a student population of 250. Accordingly, the sampling method was cluster random. Library and field methods were used to collect data. Considering that all the questionnaires used in the present study have been reviewed by university professors and experts and their validity and reliability have been measured; the researcher personally took action on the validity and reliability of research tools to improve the validity of the questionnaires.Discussion and ResultsStructural equation modeling has been used for analysis. Since the root mean index of the mean squared is approximately 0.037, the model has a good fit. Other goodness-of-fit indicators have also been accepted in the range. The strength of the relationship between psychological toughness and school bonding has been calculated to be equal to (0.79), indicating that the correlation is favorable. The t-test of the test (8.83) was obtained which is greater than the critical value of t at the 5% error level (1.96) and shows that the observed correlation is significant. Therefore, it can be said that there is a positive and significant relationship between students' psychological toughness and their connection to school. Also, the calculated strength of the relationship between school and aggression is equal to (-0.83), which indicates that the correlation is favorable. The t-test of the test (-9.72) was also obtained, which is smaller than the critical value of t at the 5% error level (-1.96) and shows that the observed correlation is significant. Therefore, it can be said that there is a negative and significant relationship between students' connection with school and their aggression. Also, the strength of the relationship between psychological toughness and aggression has been calculated equal to (-0.52), which indicates that the correlation is favorable.